KEEFEKTIFAN PEMBELAJARAN MENULIS CERPEN MELALUI MEDIA STORY WHEEL DAN MEDIA DIGITAL DIARY DENGAN MODEL PROJECT BASED LEARNING PADA SISWA SMA - Aprilia, Rizky; Zuliyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of short story writing learning using Storywheel and Digital Diary media and to see the improvement in student learning outcomes after the application of both media. The study used a quantitative method with a quasi experiment design, with analysis in the form of normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, and N-Gain calculations. The results of the N-Gain calculation show that Storywheel media obtained an average score of 0.55 with an N-Gain percent of 55.06%, which is included in the moderate category; while Digital Diary obtained an average score of 0.55 with an N-Gain percent of 54.80%, also in the moderate category towards less effective. The results of the paired sample t-test in both classes showed a significant difference between the pretest and posttest scores, while the independent sample t-test showed that there was no significant difference in effectiveness between the use of the two media. Overall, this study concludes that Storywheel and Digital Diary are able to improve students' short story writing skills at a moderate level, although their effectiveness has not yet reached the high category. Keyword : Writing Learning, Story Wheel, Digital Diary